Evidence-based clinical guidelines for eating disorders: international comparison - Hilbert, Anja (Curr Opin Psychiatry, 2017)
PURPOSE OF REVIEW: The current systematic review sought to compare available evidence-based clinical treatment guidelines for all specific eating disorders. RECENT FINDINGS: Nine evidence-based clinical treatment guidelines for eating disorders were located through a systematic search. The international comparison demonstrated notable commonalities and differences among these current clinical guidelines. SUMMARY: Evidence-based clinical guidelines represent an important step toward the dissemination and implementation of evidence-based treatments into clinical practice. Despite advances in clinical research on eating disorders, a growing body of literature demonstrates that individuals with eating disorders often do not receive an evidence-based treatment for their disorder. Regarding the dissemination and implementation of evidence-based treatments, current guidelines do endorse the main empirically validated treatment approaches with considerable agreement, but additional recommendations are largely inconsistent. An increased evidence base is critical in offering clinically useful and reliable guidance for the treatment of eating disorders. Because developing and updating clinical guidelines is time-consuming and complex, an international coordination of guideline development, for example, across the European Union, would be desirable.